Diet-induced obesity dampens the temporal oscillation of hepatic mitochondrial lipids - Rashi Jain; Rajprabu Rajendran; Sona Rajakumari (Journal of Lipid Research)
Mitochondria play a pivotal role in energy homeostasis and regulate several metabolic pathways. The inner and outer membrane of mitochondria comprises unique lipid composition and proteins that are essential to form electron transport chain complexes, orchestrate oxidative phosphorylation, β-oxidation, ATP synthesis, etc. As known, diet-induced obesity affects mitochondrial function, dynamics, and mitophagy, which are governed by circadian clock machinery. Though DIO impairs the interplay between circadian oscillation and lipid metabolism, the impact of DIO on mitochondrial membrane lipid composition and their temporal oscillation is unknown. Thus, we investigated the diurnal oscillation of liver mitochondrial lipidome at various Zeitgeber times using quantitative lipidomics. Our data suggested that obesity disrupted lipid accumulation profiles and diminished the oscillating lipid species in the hepatic mitochondria. Strikingly, HFD manifested a more homogenous temporal oscillation pattern in phospholipids regardless of possessing different fatty acyl-chain lengths and degrees of unsaturation. In particular, DIO impaired the circadian rhythmicity of phosphatidyl ethanolamine, phosphatidyl choline, phosphatidyl serine, and ether-linked phosphatidyl ethanolamine. Also, DIO altered the rhythmic profile of PE/PC, ePE/PC, PS/PC ratio, and key proteins related to mitochondrial function, dynamics, and quality control. Since HFD dampened lipid oscillation, we examined whether the diurnal oscillation of mitochondrial lipids synchronized with mitochondrial function. Also, our data emphasized that acrophase of mitochondrial lipids synchronized with increased oxygen consumption rate and Parkin levels at ZT16 in chow-fed mice. Our study revealed that obesity altered the mitochondrial lipid composition and hampered the rhythmicity of mitochondrial lipids, oxygen consumption rate, and Parkin levels in the liver.